1990
DOI: 10.2307/2409343
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Host Range Evolution: Colonization of Coronilla varia by Colias philodice (Lepidoptera: Pieridae)

Abstract: The evolution of host plant range is of both theoretical and economic importance, since present associations between insect herbivores and their host plants are largely attributable to past host shifts and host range expansions. Although the evolutionary lability of host plant range among herbivorous insects has long been recognized (Dethier, 1954; Ehrlich and Raven, 1964), the study of host range evolution among herbivorous insects remains essentially a post hoc science. However, as argued by Gould (1978, 198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 30 publications
(36 reference statements)
2
58
0
Order By: Relevance
“…When experiments were made on established and novel host plants, the results from previous experiments on other herbivorous insects indicate positive or no genetic correlation (Rausher, 1984b;Via, 1984;Hare & Kennedy, 1986;James et al, 1988;Karowe, 1990;Fox, 1993), and significant genetic variation in growth performance on each plant (Rausher, 1984b;Hare & Kennedy, 1986). These and the present results suggest that host expansion may not be constrained genetically at least at the initial stage of host range evolution.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…When experiments were made on established and novel host plants, the results from previous experiments on other herbivorous insects indicate positive or no genetic correlation (Rausher, 1984b;Via, 1984;Hare & Kennedy, 1986;James et al, 1988;Karowe, 1990;Fox, 1993), and significant genetic variation in growth performance on each plant (Rausher, 1984b;Hare & Kennedy, 1986). These and the present results suggest that host expansion may not be constrained genetically at least at the initial stage of host range evolution.…”
Section: Discussionsupporting
confidence: 51%
“…However, negative correlations have been found in only a limited number of species (Gould, 1979;Fry, 1990;Via, 1991;Mackenzie, 1996). Instead of a negative genetic correlation, positive or no genetic correlations were commonly reported in the previous studies (Rausher, 1984b;Via, 1984;Hare & Kennedy, 1986;Futuyma & Philippi, 1987;James et al 1988;Jaenike, 1989;Karowe, 1990;Fox, 1993;Lu et al 1997). To account for this general lack of negative genetic correlations, it has been suggested that antagonistic pleiotropic effects reflecting underlying constraints may be masked by several factors that increase genetic variation in general performance across hosts (Service & Rose, 1985;Houle, 1991;Price & Schluter, 1991;Fry, 1993).…”
Section: Introductionmentioning
confidence: 94%
“…They are important because they can act as postmating isolating barriers. However, there is surprisingly little empirical support for trade-offs in phytophagous insects (Futuyma and Moreno 1988;Jaenike 1990; for exceptions see Gould 1979;Mitter et al 1979;Fry 1990;Karowe 1990;Via 1991;and Mackenzie 1996). Ifthe current dearth of examples is an accurate reflection of nature, then sympatric speciation via host shifts is an uncommon mode of divergence (Butlin 1987).…”
mentioning
confidence: 99%
“…Łukowski et al 2017), develop as well as or better than they would if feeding on native host plants (e.g. Karowe 1990;Hull-Sanders et al 2007;Chupp and Battaglia 2014). Other researchers have Communicated by Livy Williams.…”
Section: Introductionmentioning
confidence: 99%